The Balance between Conventional DCs and Plasmacytoid DCs Is Pivotal for Immunological Tolerance during Pregnancy in the Mouse - Fang, Wen-ning (Sci Rep, 2016)
Dendritic cells (DCs), which can shape their functions depending on the microenvironment, are crucial for the delicate balance of immunity and tolerance during pregnancy. However, the mechanism underlying the microenvironment-educated plasticity of DC differentiation during pregnancy remains largely unclear. Here, we found that the differentiation of conventional DCs (cDCs) and plasmacytoid DCs (pDCs) is regulated in a tissue-specific manner during pregnancy. The ratio of cDCs and pDCs remained constant in the spleen. However, the ratio changed in the para-aortic lymph nodes (LNs), where cDC percentages were significantly reduced concurrent with an increase in pDCs from E8.5 to E16.5. Moreover, the expansion of pDCs and T regulatory (Treg) cells was correlated in the para-aortic LNs, and pDCs had more potential to induce regulatory T cells (Tregs) compared with cDCs (independent of IDO expression). Notably, the balance between cDCs and pDCs is disrupted in IFN-γ-induced abnormal pregnancy, accompanied by lower Treg percentages in the para-aortic LNs and decidua. To further identify the underlying mechanism, we found that elevated IFN-γ can increase the levels of GM-CSF to alter the differentiation of pDCs into cDCs in vivo. Therefore, we provide a novel regulatory mechanism underlying pregnancy-related immune tolerance that involves the balance of DC subsets, which may offer a new target for the prevention of human spontaneous abortion.